2020
DOI: 10.1044/2019_jslhr-19-00219
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Input Parameters in an Expressive Vocabulary Treatment With Late Talkers

Abstract: Purpose The aims of this study were (a) to assess the efficacy of the Vocabulary Acquisition and Usage for Late Talkers (VAULT) treatment and (b) to compare treatment outcomes for expressive vocabulary acquisition in late talkers in 2 conditions: 3 target words/90 doses per word per session versus 6 target words/45 doses per word per session. Method We ran the treatment protocol for 16 sessions with 24 primarily monolingual English-speaki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 36 publications
0
10
1
3
Order By: Relevance
“…These studies used different intervention approaches than the present study and each other, and their treatments were longer and/or more intensive than the present research. The participants in three of these studies [6,7,18] showed two to three times greater increases in their expressive vocabularies than those in the present study. LTs in the other two studies increased their expressive vocabularies by as many or fewer words than those in the present research [21,26].…”
Section: Impacts Of the Interventioncontrasting
confidence: 62%
See 4 more Smart Citations
“…These studies used different intervention approaches than the present study and each other, and their treatments were longer and/or more intensive than the present research. The participants in three of these studies [6,7,18] showed two to three times greater increases in their expressive vocabularies than those in the present study. LTs in the other two studies increased their expressive vocabularies by as many or fewer words than those in the present research [21,26].…”
Section: Impacts Of the Interventioncontrasting
confidence: 62%
“…Alt and colleagues published two statistical learning-based studies designed to increase the expressive vocabularies of LTs [6,7]. Although neither addressed shape bias specifically, they are included here to demonstrate the potential for this category of intervention.…”
Section: Statistical Learning and Shape Biasmentioning
confidence: 99%
See 3 more Smart Citations